Determinants of Zakat Contribution Amounts: Evidence from Muzakki at Daarut Tauhiid (DT) Peduli Cirebon - Dini Nadila Sari; Syaeful Bakhri; Nursyamsudin (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
This study aims to analyze the influence of socio-economic characteristics on the amount of zakat paid by muzakki (Zakkah Payers) in Daarut Tauhiid (DT) Peduli. Zakat is not only a form of spiritual worship, but also serves as a tool to reduce social inequality and improve community welfare. In Indonesia, although the potential for zakat from income and services is quite large, its realization is still relatively low. Socio-economic characteristics such as education, occupation, income, and number of dependents influence the amount of zakat paid, so understanding these factors is important for zakat management institutions to design effective and targeted collection and distribution strategies. The study used a quantitative method with a survey approach. The study population consisted of 136 zakat payers, with a sample of 60 people selected through purposive sampling using the Slovin formula. Data were obtained through questionnaires and analyzed using multiple linear regression, partial t-test, simultaneous F-test, and coefficient of determination. The results showed that education, occupation, and income had a significant effect on the amount of zakat paid, but the number of breadwinners did not have a significant effect. Simultaneously, socioeconomic characteristics had a positive and significant effect, confirming that the combination of education, occupation, and income determines the amount of zakat paid by zakat payers. This finding demonstrates the importance of considering the socio-economic characteristics of zakat payers to achieve success in zakat management and its impact on societal welfare.